Thrombocytopenia and Postpartum Hemorrhage in a Woman with Chromosome 22q11.2 Deletion Syndrome - Sarah L. Pachtman; Kathy Deng; Deepak Nanda (Hindawi Limited, 2016)
Chromosome 22q11.2 deletion syndrome, also known as DiGeorge or velocardiofacial syndrome, is associated with a wide spectrum of phenotypic features. It is known to be associated with severe macrothrombocytopenia. Postpartum hemorrhage is a leading cause of maternal morbidity and mortality globally. Chromosome 22q11.2 deletion syndrome is rare cause of thrombocytopenia that can be a significant risk factor for life-threatening postpartum hemorrhage. We report a case of postpartum hemorrhage in a woman with 22q11.2 deletion syndrome causing severe macrothrombocytopenia.